An updated checklist of the ants of India with their specific distributions in Indian states (Hymenoptera, Formicidae) - Bharti, Himender (Zookeys, 2016)
Abstract. As one of the 17 megadiverse countries of the world and with four biodiversity hotspots represented in its borders, India is home to an impressive diversity of life forms. However, much work remains to document and catalogue the species of India and their geographic distributions, especially for diverse invertebrate groups. In the present study, a comprehensive and critical list of Indian ant species is provided with up-to-date state-wise distribution. A total of 828 valid species and subspecies names belonging to 100 genera are listed from India. Potential erroneous data, misidentifications and dubious distributional records that may exist in the literature are also identified. The present exhaustive listing of Indian ants will provide a holistic view about diversity and distribution and will also help to identify major undersampled areas where future sampling and taxonomic efforts should be directed.